2010
DOI: 10.3945/ajcn.2009.27881
|View full text |Cite
|
Sign up to set email alerts
|

l-Arginine supplementation improves exercise capacity after a heart transplant

Abstract: Oral LAS may be a useful adjuvant therapeutic to improve quality of life and exercise tolerance in HTx recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…As previously reported [3,4,25], postischaemic forearm vasodilatation, markedly reduced at baseline, was significantly increased during l ‐arg treatment. Our data are in line with a recent publication by Doutreleau et al The authors report that a 6‐week intake of oral l ‐arg is able to improve endothelial function, skeletal muscle vasodilatation, oxygen delivery and extraction during exercise in heart transplant recipients, suggesting a beneficial role of l ‐arg in improving exercise tolerance [26].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As previously reported [3,4,25], postischaemic forearm vasodilatation, markedly reduced at baseline, was significantly increased during l ‐arg treatment. Our data are in line with a recent publication by Doutreleau et al The authors report that a 6‐week intake of oral l ‐arg is able to improve endothelial function, skeletal muscle vasodilatation, oxygen delivery and extraction during exercise in heart transplant recipients, suggesting a beneficial role of l ‐arg in improving exercise tolerance [26].…”
Section: Discussionsupporting
confidence: 86%
“…In addition, participants having l-arg treatment showed a more pronounced reduction in FM and waist circumference with spare of FFM as compared with subjects of the placebo group. Similar results have been found in animal studies where l-arg reduced body-fat accretion, enhanced muscle gain and improved the metabolic profile [1,2,24] As previously reported [3,4,25], postischaemic forearm vasodilatation, markedly reduced at baseline, was significantly increased during l-arg treatment. Our data are in line with a recent publication by Doutreleau et al The authors report that a 6-week intake of oral l-arg is able to improve endothelial function, skeletal muscle vasodilatation, oxygen delivery and extraction during exercise in heart transplant recipients, suggesting a beneficial role of l-arg in improving exercise tolerance [26].…”
Section: Eighteen-month Treatment Periodsupporting
confidence: 88%
“…Increased NO might be due to an upregulation of eNOS or its enhanced activity. Other mechanisms are proposed, such as an increase in plasma antioxidant activity (Franzoni et al, 2004) that prevent the scavenging of NO by free radicals and increase the bioavailability of its precursors (Doutreleau et al, 2010) and cofactors and thus increase its bioavailability. Apart from changes in the bioavailability of NO, an increase of other vasodilators, such as prostanoids (McCord et al, 2006) and EDHF (Taddei et al, 2006), may also be involved.…”
Section: Exercise Augments the Endothelium Dependent Vasodilation In mentioning
confidence: 99%
“…In fact, recent research has shown evidence that Arg supplementation can restore NO in patients who have experienced a heart event or have recently undergone a transplant. For example, in heart transplant recipients, oral L-Arg supplementation stimulated the NO pathway and restored endothelial function, and thus exercise capacity [38], which can both be severely reduced after such an event [39]. Further, an intravenous infusion of L-Arg improved endothelial dysfunction of both the heart microvasculature and epicardial coronary arteries in cardiac transplant recipients [40].…”
Section: Heart Healthmentioning
confidence: 97%